Towards an agenda to investigate language development in an indigenous group in the Amazon - Claudia Uller; Marília Facó Soares (Revista Linguística, 2022)
The present work advances a research agenda within the broader field of language and cognition for the study of the expression of numerical concepts in early development.  Lying at the core of the proposed agenda is the question of the relationship between the acquisition of the first language and the expression of numerical concepts in infancy.  Two processes exist to explain the expression of numerical information in languages. The first takes place through the grammatical structure of language (its quantificational system). The second is the direct expression of number with the use of number language expressions. The first process is called “grammatical number”, the second, “linguistic number”. In an attempt to raise questions that lie beyond previous investigations, and to expand linguistic and cognitive considerations, the proposal includes discussions regarding various numerical abilities in differing linguistic contexts in light of conceptual development of number systems. We hope this proposal will raise interesting cognitive and linguistic issues within the scope of languages spoken by native Amazonian peoples.